Genome-wide survey of the bHLH super gene family in Brassica napus - Ke, Yun-Zhuo (BMC Plant Biol, 2020)
BACKGROUND: The basic helix-loop-helix (bHLH) gene family is one of the largest transcription factor families in plants and is functionally characterized in diverse species. However, less is known about its functions in the economically important allopolyploid oil crop, Brassica napus. RESULTS: We identified 602 potential bHLHs in the B. napus genome (BnabHLHs) and categorized them into 35 subfamilies, including seven newly separated subfamilies, based on phylogeny, protein structure, and exon-intron organization analysis. The intron insertion patterns of this gene family were analyzed and a total of eight types were identified in the bHLH regions of BnabHLHs. Chromosome distribution and synteny analyses revealed that hybridization between Brassica rapa and Brassica oleracea was the main expansion mechanism for BnabHLHs. Expression analyses showed that BnabHLHs were widely in different plant tissues and formed seven main patterns, suggesting they may participate in various aspects of B. napus development. Furthermore, when roots were treated with five different hormones (IAA, auxin; GA(3), gibberellin; 6-BA, cytokinin; ABA, abscisic acid and ACC, ethylene), the expression profiles of BnabHLHs changed significantly, with many showing increased expression. The induction of five candidate BnabHLHs was confirmed following the five hormone treatments via qRT-PCR. Up to 246 BnabHLHs from nine subfamilies were predicted to have potential roles relating to root development through the joint analysis of their expression profiles and homolog function. CONCLUSION: The 602 BnabHLHs identified from B. napus were classified into 35 subfamilies, and those members from the same subfamily generally had similar sequence motifs. Overall, we found that BnabHLHs may be widely involved in root development in B. napus. Moreover, this study provides important insights into the potential functions of the BnabHLHs super gene family and thus will be useful in future gene function research.